2016
DOI: 10.1175/mwr-d-15-0429.1
|View full text |Cite
|
Sign up to set email alerts
|

Tropical and Extratropical Controls of Gulf of California Surges and Summertime Precipitation over the Southwestern United States

Abstract: In this study ERA-Interim data are used to study the influence of Gulf of California (GoC) moisture surges on the North American monsoon (NAM) precipitation over Arizona and western New Mexico (AZWNM), as well as the connection with larger-scale tropical and extratropical variability. To identify GoC surges, an improved index based on principal component analyses of the near-surface GoC winds is introduced. It is found that GoC surges explain up to 70% of the summertime rainfall over AZWNM. The number of surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 82 publications
1
23
0
Order By: Relevance
“…For the AM, additional maximum RPSS during phases 6, 8, 1, and 2 indicate bettter skill for monsoon breaks compared to active episodes most frequent during phase 4 and for which skill is minimum, in agreement with greater spatial coherence and predictability than for the core of the monsoon season (Moron et al, 2017). For the NAM and WAM, skill is minimum during MJO phase 3 when convection is enhanced over the Indian Ocean, in turn increasing the activity of AEWs within the WAM and tropical Atlantic TCs (Zhang, 2013;Klotzbach and Oliver, 2015) linked to Gulf moisture surges feeding in the NAM (Pascale and Bordoni, 2016), which synoptic nature might be less predictible. Contrasting skill relationships to MJO phases 7 and 3-4 suggest potential skill improvement when RMM1 and RMM2 are respectively negative and positive, consistently with mean RPSS and PC1 correlations with MJO RMMs for the AM and WAM in particular.…”
Section: Discussionmentioning
confidence: 59%
“…For the AM, additional maximum RPSS during phases 6, 8, 1, and 2 indicate bettter skill for monsoon breaks compared to active episodes most frequent during phase 4 and for which skill is minimum, in agreement with greater spatial coherence and predictability than for the core of the monsoon season (Moron et al, 2017). For the NAM and WAM, skill is minimum during MJO phase 3 when convection is enhanced over the Indian Ocean, in turn increasing the activity of AEWs within the WAM and tropical Atlantic TCs (Zhang, 2013;Klotzbach and Oliver, 2015) linked to Gulf moisture surges feeding in the NAM (Pascale and Bordoni, 2016), which synoptic nature might be less predictible. Contrasting skill relationships to MJO phases 7 and 3-4 suggest potential skill improvement when RMM1 and RMM2 are respectively negative and positive, consistently with mean RPSS and PC1 correlations with MJO RMMs for the AM and WAM in particular.…”
Section: Discussionmentioning
confidence: 59%
“…As in Pascale and Bordoni (2016), the focus of this study is on the influence of GoC surges on precipitation over AZWNM, defined as the area between 1148 and 1088W and between 318 and 368N (Fig. 1).…”
Section: B Observationsmentioning
confidence: 99%
“…While modulated by daytime heating, AZWNM convective activity also features synoptic to submonthly variability (Berbery and Fox-Rabinovitz 2003;Wu et al 2009;Pascale and Bordoni 2016), as revealed by significant spectral peaks in Arizona rainfall in the 5-20-day band or even longer time scales (e.g., Cavazos et al 2002;Nolin and Hall-McKim 2006). Synoptic-scale convective activity over AZWNM tends to be preceded by Gulf of California (GoC) moisture surges (or simply GoC surges).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations